Concept and utility of population pharmacokinetic and pharmacokinetic/ pharmacodynamic models in drug development and clinical practice - Roganović, Maša; Homšek, Ana; Jovanović, Marija; Topić Vučenović, Valentina; Ćulafić, Milica; Miljković, Branislava; Vučićević, Katarina (Archives of Pharmacy, 2021)
Due to frequent clinical trial failures and consequently fewer new drug approvals, the need for improvement in drug development has, to a certain extent, been met using model-based drug development. Pharmacometrics is a part of pharmacology that quantifies drug behaviour, treatment response and disease progression based on different models (pharmacokinetic - PK, pharmacodynamic - PD, PK/PD models, etc.) and simulations. Regulatory bodies (European Medicines Agency, Food and Drug Administration) encourage the use of modelling and simulations to facilitate decision-making throughout all drug development phases. Moreover, the identification of factors that contribute to variability provides a basis for dose individualisation in routine clinical practice. This review summarises current knowledge regarding the application of pharmacometrics in drug development and clinical practice with emphasis on the population modelling approach.
Keywords: pharmacometrics; population analysis; pharmacokinetics; pharmacokinetic-pharmacodynamic modelling